2012
DOI: 10.1073/pnas.1117557109
|View full text |Cite
|
Sign up to set email alerts
|

How Christians reconcile their personal political views and the teachings of their faith: Projection as a means of dissonance reduction

Abstract: The present study explores the dramatic projection of one's own views onto those of Jesus among conservative and liberal American Christians. In a large-scale survey, the relevant views that each group attributed to a contemporary Jesus differed almost as much as their own views. Despite such dissonance-reducing projection, however, conservatives acknowledged the relevant discrepancy with regard to “fellowship” issues (e.g., taxation to reduce economic inequality and treatment of immigrants) and liberals ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Another group of researchers (Ross, Lelkes, & Russell, 2012) obtained a similar result: Christian adults perceived Jesus (who is portrayed as God or God's son in Christian traditions) to hold the same ideological beliefs they did, but more strongly. That is, liberal Christians reported that a contemporary Jesus would hold an even more liberal ideology, while conservative Christians reported that a contemporary Jesus would hold an even more conservative ideology.…”
Section: Adults' Implicit Representations Of God's Mindmentioning
confidence: 78%
See 1 more Smart Citation
“…Another group of researchers (Ross, Lelkes, & Russell, 2012) obtained a similar result: Christian adults perceived Jesus (who is portrayed as God or God's son in Christian traditions) to hold the same ideological beliefs they did, but more strongly. That is, liberal Christians reported that a contemporary Jesus would hold an even more liberal ideology, while conservative Christians reported that a contemporary Jesus would hold an even more conservative ideology.…”
Section: Adults' Implicit Representations Of God's Mindmentioning
confidence: 78%
“…The literature on anchoring and adjustment in reasoning shows that people often make estimates of unknown quantities by “anchoring” on salient information and then adjust insufficiently, leading to final estimates that remain close to the original anchor (e.g., Ariely, Loewenstein, & Prelec, 2006; Epley & Gilovich, 2004, 2005; Tamir & Mitchell, 2013; Tversky & Kahneman, 1974). If people anchor on human minds in general or on their own minds in particular (e.g., Epley et al, 2009; Ross et al, 2012) and then adjust to represent God's mind, their final representation of God's mind may still largely resemble that of human minds.…”
Section: Why Adults Anthropomorphize Godmentioning
confidence: 99%
“…Yet, a full‐fledged understanding of the distinction between God's extraordinary mind and human minds entails a protracted developmental process, and even adults often revert to thinking about God's mind as being human‐like (Heiphetz, Lane, Waytz, & Young, ). Moreover, U.S. adults hold egocentric views of God's ideological beliefs (e.g., about abortion), perceiving such beliefs as especially similar to their own (Epley, Converse, Delbosc, Monteleone, & Cacioppo, ; Ross, Lelkes, & Russell, ). The current work builds on these studies to extend theoretical understanding of belief attribution in two ways: (1) investigating attributions of moral beliefs to different agents and (2) testing children as well as adults with the same paradigm to gain greater insight into age‐related differences and similarities in belief attribution.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we tested three possibilities regarding children's and adults' judgments about God's mind. Participants may report that they and God are similar to each other and different from other people (Epley et al, 2009;Ross et al, 2012). However, participants may report that their beliefs differ from those held by God and other people.…”
mentioning
confidence: 99%
“…The notion of rationalization as a collective process came out in a recent study (7), wherein the work by Ross et al (7) explored the interplay between Christianity and politics in the United States. In particular, Ross was intrigued by how people reconciled their liberal or conservative political views with their religious values.…”
Section: Conflict Resolutionmentioning
confidence: 99%